Improving Youths' Attitudes About the Police: Results From an Experimental Design. (December 2019) - Freiburger, Tina L.
This study examined the effectiveness of Students Talking it Over with Police (STOP) to improve youths' perceptions of the police, willingness to cooperate with police, and perceptions of procedural justice. It utilized an experimental design in 36 schools in Milwaukee, WI. Pretest and posttest were administered to assess the outcomes before and after the STOP program. The results indicated that STOP was effective in improving youths' perceptions of the police, youths' willingness to cooperate with the police, and youths' perceptions of procedural justice. Additional analysis suggested that STOP was able to reverse some of the negative effects these encounters had on youths' perceptions, as those with prior negative interactions of police experienced significantly greater rates of change in their perceptions of procedural justice than those who did not have a negative encounter.